Dynamics of some biochemical indices in myocardial infarction treated with thrombolysis and creatine phosphate - Weinbergová, O; Zeman, K; Komárek, J; Kölbel, F; Metelka, R; Ostranský, J (Acta Universitatis Palackianae Olomucensis Facultatis Medicae, 1996)
There was studied the effect of intravenously administered creatin phosphate (Neoton-drug with cardioprotective effect, Alfa Schiapparelli Wassermann) in the group of 98 patients affected by their first attack of myocardial infarction. In the course of the treatment there were observed the serum level of many biochemical indices, including the cardioselective enzyme activity. We concluded that the patients treated with Neoton, compared with the control group, revealed the significantly higher elevation of the CK, AST and LDH activity levels and the shift of the CK peak activity towards to the earlier hours after the onset of anginal pain.
Keywords: fibrinolytika; Female; Phosphocreatine; Fibrinolytic Agents; Humans; ženské pohlaví; fosfokreatin; mužské pohlaví; Male; lidé; Middle Aged; lidé středního věku; infarkt myokardu; Myocardial Infarction